2019 IEEE Conference on Games (CoG) 2019
DOI: 10.1109/cig.2019.8848123
|View full text |Cite
|
Sign up to set email alerts
|

Your Gameplay Says It All: Modelling Motivation in Tom Clancy’s The Division

Abstract: Is it possible to predict the motivation of players just by observing their gameplay data? Even if so, how should we measure motivation in the first place? To address the above questions, on the one end, we collect a large dataset of gameplay data from players of the popular game Tom Clancy's The Division. On the other end, we ask them to report their levels of competence, autonomy, relatedness and presence using the Ubisoft Perceived Experience Questionnaire. After processing the survey responses in an ordina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 53 publications
1
28
0
Order By: Relevance
“…These results indicate a slight linear relationships between certain behaviors and motivational regulation. This is not surprising, as previous research examining game metrics and self-reported experience measures also reported low to medium correlations (Canossa et al, 2013 ; Schaekermann et al, 2017 ; Melhart et al, 2019 ). Among the 14 metrics we studied, the four motivational profiles varied significantly in terms of their winrate and assists in unranked matches, and kill-death-assist ratios in ranked matches (see also Table 3 and Figure 4 ).…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…These results indicate a slight linear relationships between certain behaviors and motivational regulation. This is not surprising, as previous research examining game metrics and self-reported experience measures also reported low to medium correlations (Canossa et al, 2013 ; Schaekermann et al, 2017 ; Melhart et al, 2019 ). Among the 14 metrics we studied, the four motivational profiles varied significantly in terms of their winrate and assists in unranked matches, and kill-death-assist ratios in ranked matches (see also Table 3 and Figure 4 ).…”
Section: Discussionmentioning
confidence: 60%
“…The aim of this study was to explore how players' underlying motivational regulations relate to their experience and in-game behavior in a MOBA game. In contrast to previous research on predicting motivation from in-game metrics (Melhart et al, 2019 ), we present a novel, theory-driven approach for detecting motivational profiles, and compare these in terms of player experience and in-game behavior.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, companies are more and more collaborating with research institutions, to bring the latest innovations out to the industry. For example, Massive Entertainment and the University of Malta collaborated to predict the motivations of players in the popular game Tom Clancys The Division [49]. Other companies, such as King, are investing heavily in deep learning methods to automatically learn models of players that can then be used for playtesting new levels quickly [25].…”
Section: Journals Conferences and Competitionsmentioning
confidence: 99%